KEMAMPUAN ISOLAT BAKTERI PENGHASIL INDOLE ACETIC ACID (IAA) DARI TANAH GAMBUT SAMPIT KALIMANTAN TENGAH - Sofyan Fauzi Larosa; Endang Kusdiyantini; Budi Raharjo; Antonius Sarjiya (Jurnal Akademika Biologi, 2013)
Peat soil is present in many areas of Indonesia, one of them is in Sampit regency Central Kalimantan. Peat soil is a type of soil which has an extreme characteristic  of pH  around 3-5. However, it is presumed that there is bacteria that can produce growth hormones, such as  IAA. This study aimed to determine the ability of bacterial  isolated from peat garden and burned area in Sampit regency which could  produce IAA. Several tests were carried out including bacterial isolation, purification isolates, growth at different pH conditions, as well as IAA production with the addition of L-Tryptophan precursors with different concentrations. The  growth and concentration of IAA was measured  using spectrophotometry with wavelength 600 nm to 530 nm for growth and IAA, respectively. Results showed that  five isolates produced IAA, three isolates from peat garden area and two isolates from burned areas. All isolates showed the highest growth at pH 6, and the highest IAA production  at  43.311 ppm was produced by TGK6  isolate with the addition of 300 ppm L-Tryptophan. Keywords: Indole Acetic Acid, Peat Soil, L-Tryptophan